The value of supplementary trace minerals and trace minerals plus bonemeal in a fattening ration - Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This is the fifth experiment in this series conducted to determine the value of added trace minerals in a typical cattle-fattening ration. The four previous experiments are reported in Kansas Agricultural Experiment Station Circulars 279, 308, 335, and 358. No response has been obtained when trace minerals were added to high roughage rations of sorghum silage, sorghum grain and a protein concentrate, or to a fattening ration or sorghum grain, prairie hay, and a protein concentrate. Improved performance has been obtained when trace minerals were added to fattening rations of corn, prairie hay, and a protein concentrate. Ground limestone has been fed in all the fattening trials to furnish adequate calcium.
Keywords: Beef; Trace minerals; Bonemeal; Ration